Biofuels and Food Security: Micro-evidence from Ethiopia - Martha Negash; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
This paper provides microeconomic evidence on food security impacts of privately organized biofuel outgrower schemes in Ethiopia. We conducted a household and community level survey and evaluated the impact of castor bean firming. We use endogenous switching regressions to analyze the impact on food security. Food security (as measured by a ?food gap?) and food caloric intake is significantly better in households producing castor beans. ?Fuel? and ?food? are complements rather than substitutes at the micro-level in castor production in Ethiopia.
Keywords: Q42; Q16; O13; Q12; 330; biofuel; castor; food security; Ethiopia